Review of Pharmacological Properties, Phytochemistry and Medicinal uses of Volkameria glabra - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Volkameria glabra (E. Mey.) Mabb. & Y.W. Yuan is a deciduous shrub or a small tree widely used as traditional medicine throughout its distributional range in tropical Africa. This study is aimed at providing a critical review of pharmacological properties, phytochemistry, and medicinal uses of V. glabra. Documented information on pharmacological properties, phytochemistry and medicinal uses of V. glabra was collected from several online sources such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as book chapters, books, journal articles and scientific publications obtained from the university library. This study revealed that the bark, leaf and root infusion and/or decoction of V. glabra are mainly used as immune booster, protective charm, anthelmintic and ethnoveterinary medicine, and traditional medicine for convulsions, fractured bones, fever, wounds, gastro-intestinal problems, snake bite and respiratory diseases. Phytochemical compounds identified from the species include aliphatic glycosides, anthraquinones, cardiac glycosides, flavonoids, iridoid, phenols, saponins, steroids, tannins and triterpenoids. The V. glabra and compounds isolated from the species exhibited acaricidal, anthelmintic, antibacterial, antifungal, antimycobacterial, anti-collagenase, antidiabetic, anti-elastase, anti-inflammatory, antileishmanial, antioxidant, antiplasmodial, antipyretic, cholinesterase enzyme inhibition, immune-stimulant and cytotoxicity activities. Volkameria glabra should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.